Holistic-comprehensive approaches to improve nutritional status of children under five years - Febri Endra Budi Setyawan; Retno Lestari (SAGE Publishing, 2021)
Background: Malnutrition has been identified as the leading cause of illness and death in almost half of children under 5 years. Hence, to prevent the impact of malnutrition on physical and psychological development, family physicians need to explore new approaches in the health care delivery models that go beyond the scope of practice. A holistic-comprehensive approach will help the physicians develop a more thorough assessment of nutritional status. This study aims to determine factors associated with the nutritional status of children under five years using holistic-comprehensive approaches. Design and Methods: A case-control design was implemented, with emphasis on the identification of cases and control groups; 48 children confirmed malnutrition cases and 48 control without malnutrition were recruited from a Community Integrated Health Center in East Java, Indonesia. The characteristics of agent, host and environment between groups were compared and analyzed using correlation coefficients, odds ratio, logistic regression analysis, and Structural Equation Modeling-Partial Least Square (SEM-PLS). Results: The SEM-PLS results showed that environmental factors have a greater influence on nutritional status (t-value >1.96), compared to the host factors. Furthermore, environmental factors having significant associations with nutritional status were poor socioeconomic status, low maternal educational level and not having exclusive breastfeeding. Also, the results of correlation coefficients and OR showed that birth weight (p=0.000, OR=33) and socioeconomic status (p=0.000, OR=22.3) had strong correlations with nutritional status. Conclusion: Holistic-comprehensive approaches can be used as new ways to determine factors that may be associated with nutritional status of children under 5 years of age.